Framtidens skogsbruksplan - Hallquist, Ronny (SLU/School for Forest Management, 2018)
Development of forestry management plans has been a concern during the last couple of years. In 2006 Skogforsk did a study that showed that the forestry management plan needed to be further developed. During 2017 a degree project was conducted on forest owners that owned forests in other communities than where they lived. These forest owners make up for a big part of the clientele for today’s forest federations. The study done was based upon what services they appreciated. The result was that management plans were valued low but at the same time they were demanded as an overview of the forest and for the forest plan. This was the reason why this study was conducted, to further assess how modern forest owners wish to have their management plan presented.